Distribution of heavy metals and escherichia coli in Sabak beach and Cahaya Bulan beach, Kelantan - Nurul Ain Abdullah; Rizki Wannahari; Marinah Muhammad; Mariam Firdhaus Mad Nordin (2012)
The study was carried out for determination of heavy metal and Escherichia Coli (E.Coli) in coastal water in two popular coast along Kota Bharu, Kelantan. The samples were collected from July until November 2011. Eight elements of heavy metals which are chromium (Cr), magnesium (Mn), Lead (Pb), ferum (Fe), nickel (Ni), zinc (Zn), Cooper (Cu) and cadmium (Cd) were analyzed using Inductively Coupled Plasma Mass Spectrometry (ICP - MS). The homogenized samples were introduced to ammonium pyrrolidine dithiocarbamate - methy isobutyl ketone (APDC - MIBK) extraction before it was analyzed by using ICP-MS. The existence of E.Coli in coastal water was determined by using Multi-tube Fermentation Technique. E.Coli used as an indicator for health risk water contact in recreational water. The consequences of heavy metals and microbial contamination in water samples were compared between both coastal which were located in Kota Bharu, Kelantan. The results show that concentration of heavy metals and Escherichia Coli oscillated in both locations of studies. Rood-mean-square Standard Division (Srsm) of heavy metals (ppm) Sabak beach verses Cahaya Bulan beach ; Mn =0.017 ;0.024,pb=0.087;0.013,fe=1.702;0.916,Zn=0.013;0.024,Cu=0.011;0.002 and Cr=0.145;0.147. From observation Sabak beach is more polluted compared with Cahaya Bulan beach this is because the residence area is closely with coastal caused by coastal arosion. Futhermore monsoon factor also lead to pollution because of raining and land and river runoff. Rainfall washed down the elements that contain in atmosphere directly into coastal water or river (Sankar et al..., 2010, Ashokkumar et al..,2009). However, the values of Srsm for E.Coli at Sabak beach and Cahaya Bulan beach are 10 and 5 MPN/100ml, respectively. As a conclusion in general the concentration metals and E.Coli were lower than standard suggested by government except for Fe but it stay consider safe for any coastal activity.